Age‐associated patterns in gray matter volume, cerebral perfusion and BOLD oscillations in children and adolescents. Issue 5 (24th January 2017) - Bray, Signe
Abstract: Healthy brain development involves changes in brain structure and function that are believed to support cognitive maturation. However, understanding how structural changes such as grey matter thinning relate to functional changes is challenging. To gain insight into structure‐function relationships in development, the present study took a data driven approach to define age‐related patterns of variation in gray matter volume (GMV), cerebral blood flow (CBF) and blood‐oxygen level dependent (BOLD) signal variation (fractional amplitude of low‐frequency fluctuations; fALFF) in 59 healthy children aged 7–18 years, and examined relationships between modalities. Principal components analysis (PCA) was applied to each modality in parallel, and participant scores for the top components were assessed for age associations. We found that decompositions of CBF, GMV and fALFF all included components for which scores were significantly associated with age. The dominant patterns in GMV and CBF showed significant (GMV) or trend level (CBF) associations with age and a strong spatial overlap, driven by increased signal intensity in default mode network (DMN) regions. GMV, CBF and fALFF additionally showed components accounting for 3–5% of variability with significant age associations. However, these patterns were relatively spatially independent, with small‐to‐moderate overlap between modalities. Independence of age effects was further demonstrated by correlating individual subject maps between modalities: CBF was significantly less correlated with GMV and fALFF in older children relative to younger. These spatially independent effects of age suggest that the parallel decline observed in global GMV and CBF may not reflect spatially synchronized processes. Hum Brain Mapp 38:2398–2407, 2017 . ©2017 Wiley Periodicals, Inc.